Diskursus Interpretasi Linguistik: Ragam Kejelasan dan Kesamaran Makna dalam Ushul Fiqh - Atik Abidah (Justicia Islamica, 2007)
This study aims to analyze the variety of clarity and ambiguity of meaning in ushul fiqh through a linguistic interpretation approach. The main focus of this study is how linguistic concepts influence the understanding of Islamic legal texts and how variations in meaning can have an impact on the formulation of law. The method used in this study is library research with a descriptive-analytical approach. The main sources of this research are classical and contemporary ushul fiqh literature that discuss linguistic aspects in legal interpretation. The results of the study show that the clarity and ambiguity of meaning in Islamic legal texts are caused by lexical, syntactic, and pragmatic context factors. Proper understanding of the linguistic aspects in ushul fiqh can reduce misunderstandings and provide flexibility in legal ijtihad. This study contributes to the discourse of Islamic legal interpretation by highlighting the importance of a linguistic approach in understanding sharia texts.